HUNTER: precision massive-neutrino search based on a laser cooled atomic source. (24th February 2021) - Martoff, C J; Granato, F; Palmaccio, V; Yu, X; Smith, P F; Hudson, E R; Hamilton, P; Schneider, C; Chang, E; Renshaw, A; Malatino, F; Meyers, P D; et al.
Abstract: We describe a project that brings together researchers from atomic physics, nuclear physics and sub-atomic particle physics, to develop a high-precision laboratory-scale experiment able to search for very weakly coupled sterile neutrinos in the mass range extending from 5–10 keV/ c 2 to several 100 keV/ c 2 . Observed neutrino flavor eigenstates are known to be quantum mixtures of at least three sub-eV/ c 2 mass eigenstates. There is a strong theoretical belief that there may exist further neutrino mass eigenstates at higher mass levels, and which, if in the keV/ c 2 mass range, might form all or part of the galactic dark matter. This has led to many searches for anomalous events in both astrophysical and particle physics experiments, and searches for distortions in beta decay spectra. The present experiment will utilize K -capture events in a population of 131 Cs atoms suspended in vacuum by a magneto-optical trap (MOT). Using AMO and nuclear physics techniques, individual events will be fully reconstructed kinematically. Normally each event would be consistent with an emitted neutrino mass close to zero, but the existence of a sterile neutrino of keV/ c 2 mass that mixes with the electron type neutrino produced in the decay would result in a separated population of events with non-zero reconstructed missing mass (up to the Q = 352 keV available energy of the reaction). Detailed calculations and simulations of all significant background processes have been made, in particular for scattering in the source itself, radiative K -capture, local radioactivity, cosmic ray muons, and knock-out of electrons by x-rays. A phase 1 of the experiment, under construction with funding from the W M Keck Foundation, has the potential to reach sterile neutrino mixing angles down to sin 2   θ ∼ 10 −4 . With further upgrades this technique could be progressively improved to eventually reach much lower coupling levels ∼10 −10, in particular reaching the level needed to be consistent with galactic dark matter below the astrophysical x-ray limits.